Incorporation of local novel feed resources in livestock feed for sustainable food security and circular economy in Africa - Chisoro, Prince; Jaja, Ishmael Festus; Assan, Never (Frontiers in Sustainability, 2023)
In livestock production, feed resources are very crucial, particularly in Africa where food security and sustainable development are major considerations. The incorporation of locally available novel feed resource alternatives can promote circular economy concepts, increase food security, and improve sustainable livestock production. This review attempts to compile the most recent information on the use of locally available novel feed sources found in Africa while assessing their potential benefits for circular economy principles and sustainable livestock production. We conducted a thorough literature search to find appropriate publications that were published between 2010 and 2022. The search was done using keywords relating to local novel feed resources, sustainable development, circular economy, livestock feed, and food security across a number of research databases, including PubMed, Scopus, and Web of Science. After the search and screening, relevant publications were chosen for inclusion based on their applicability to this review design, topicality (Africa), and regional focus. This review discovered a wide range of locally available novel feed resources, such as native plants, agricultural byproducts, food processing byproducts, and weeds, all of which have the potential to serve as alternative supplements or substitute feed sources for livestock. These resources frequently have a good nutritional composition and advantageous phytochemicals and can be obtained locally, decreasing reliance on foreign feed components. By exploiting locally accessible resources, the inclusion of these materials in livestock feed has significant potential to enhance livestock performance, lower production costs, and promote circular economy concepts in Africa. African countries' sustainable food security and circular economies stand to gain significantly from the use of locally available novel feed resources in livestock feed. However, further investigation is required to determine their nutritional worth, safety, and the best inclusion rates in livestock rations. For their implementation to be effective, it will also be essential to comprehend the socioeconomic, cultural, and environmental elements impacting their adoption. This review offers a thorough synthesis of the body of research, emphasizing the value of locally available novel feed sources in improving the production of livestock and advancing Africa's sustainable development targets.